IMPLEMENTASI MODEL INVESTIGASI KELOMPOK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS 4 UPTD SDN MORBATOH 1 SAMPANG MADURA - Imasatul Adamiyah; Mohammad Afifullah; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The research was conducted to determine the form of implementation of the group investigation model in Islamic education learning carried out at the elementary school level. This study uses a qualitative descriptive approach as a material to find out more deeply and describe the implementation of this group investigation model when applied to elementary schools. The location of this research is in UPTD SDN Morbatoh 1 in Sampang Madura Regency. Data collection techniques in this study used participatory observation, in-depth interviews, and documentation. The data analysis technique used is data condensation and data presentation. The results of this study indicate that this group investigation model is suitable to be applied in learning Islamic religious education by applying systematic steps, namely organizing students into several groups, planning several learning tasks together with students in a group that has been studied. determined, conduct an investigation by the way the teacher coordinates his students to find information, analyze and make conclusions, the four students are invited to present the results obtained and the last is the evaluation stage. The evaluation stage is used as material to see the progress of the learning process that has been implemented. Keyword: group investigation model, elementary school, islamic education.